Negative nominal rates - Dávila, Julio; Lukmanova, Elizaveta (Journal of Financial Stability, 2025)
We show the possibility of negative nominal interest rates in a general equilibrium model with financial intermediation. We establish that the decentralization of the planner’s steady state requires a zero nominal lending rate on bank loans to firms, as well as a negative nominal lending rate on central bank loans to banks. We also find that implementing the planner’s steady state requires firms to be bound by collateral requirements that limit their leverage. The key driver of the results is the very defining characteristic of banking, namely banks’ ability to create money by opening deposit accounts that borrowers can withdraw from, and that are unbacked by household deposits. Our results can be used to rationalize the ultra-low rates policy implemented by major central banks in the second half of the 2010’s and early 2020’s.